Some Observations on the Dates and Circumstances of the Fifteenth-Century Portuguese and Castilian Translations of John Gower’s Confessio Amantis - Santano Moreno, Bernardo (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen